ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAPORAN KEUANGAN POLITEKNIK NEGERI MADIUN - Risky Yulia Anggraini (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to examine the influence of company structure, company monitoring, and company performance on the quality of financial reporting in companies listed on the Indonesia Stock Exchange (IDX) in 2023. The research method used is descriptive with a quantitative approach, aiming to describe, analyze, and interpret phenomena or situations objectively. The sample of this study is manufacturing companies listed on the IDX with financial statements ending in 2023. The results showed that the company's structure had a significant and positive influence on the quality of financial reporting, with the calculated value of the company structure variable (X1) of 24,238, greater than the ttable value of 2,004. The regression coefficient value of 0.808 indicates that every increase in the company structure of 1 rupiah will improve the quality of financial reporting by 0.808 rupiah. Conversely, company monitoring does not have a significant effect on the quality of financial reporting, with the calculated value of the company monitoring variable (X2) of -0.505, smaller than the table value of 2.004, and the regression coefficient of -0.992 which shows a negative relationship. The company's performance also did not have a significant effect on the quality of financial reporting, with the calculated value of the company's performance variable (X3) of -2.536, smaller than the ttable value of 2.004, and a regression coefficient of -14.546 which showed a negative relationship.